Demographic responses to weather fluctuations are context dependent in a long‐lived amphibian. (7th June 2016) - Cayuela, Hugo; Arsovski, Dragan; Thirion, Jean‐Marc; Bonnaire, Eric; Pichenot, Julian; Boitaud, Sylvain; Miaud, Claude; Joly, Pierre; Besnard, Aurélien
Abstract: Weather fluctuations have been demonstrated to affect demographic traits in many species. In long‐lived organisms, their impact on adult survival might be buffered by the evolution of traits that reduce variation in interannual adult survival. For example, skipping breeding is an effective behavioral mechanism that may limit yearly variation in adult survival when harsh weather conditions occur; however, this in turn would likely lead to strong variation in recruitment. Yet, only a few studies to date have examined the impact of weather variation on survival, recruitment and breeding probability simultaneously in different populations of the same species. To fill this gap, we studied the impact of spring temperatures and spring rainfall on survival, on reproductive skipping behavior and on recruitment in five populations of a long‐lived amphibian, the yellow‐bellied toad ( Bombina variegata ). Based on capture–recapture data, our findings demonstrate that survival depends on interactions between age, population and weather variation. Varying weather conditions in the spring result in strong variation in the survival of immature toads, whereas they have little effect on adult toads. Breeding probability depends on both the individual's previous reproductive status and on the weather conditions during the current breeding season, leading to high interannual variation in recruitment. Crucially, we found that the impact of weather variation on demographic traits is largely context dependent and may thus differ sharply between populations. Our results suggest that studies predicting the impact of climate change on population dynamics should be taken with caution when the relationship between climate and demographic traits is established using only one population or few populations. We therefore highly recommend further research that includes surveys replicated in a substantial number of populations to account for context‐dependent variation in demographic processes.